Recent progress in Prussian blue films: Methods used to control regular nanostructures for electrochemical biosensing applications - Chu, Z.; Liu, Yu; Jin, W. (Elsevier BV, 2017)
In the last decade, Prussian blue (PB) has attracted increased scientific interest in various research fields, such as fuel cells, gas separation and pollution treatment. Due to its advanced catalysis, biocompatibility, selectivity and stability, PB has been widely used in biosensor construction. However, the formation of regular PB nanostructures is challenging due to its fast crystallization rate. Recently, developments in this research area have increased due to emerging novel synthesis methods in nanoscale technology. Various regular nanostructures of PB films that show superior biosensing performance have been prepared. In this review, recent research progress in PB nanostructures is summarized, with special emphasis on the methodology of nanostructure control. The mechanism and key factors in regular PB crystallization are also discussed for each synthesis method. The performance of PB nanostructure-based biosensors is compared with others to show the advantages of nanostructure control. The methodology discussed in this review not only include the regular growth of PB films, but also provides information on the nanostructure control of more crystalline materials, including PB analogues, noble metals, metal oxides and coordination compounds. In addition to biosensing applications and the development of more advanced nanostructures, PB has also shown increased advanced properties in other scientific areas.